1999
DOI: 10.1021/la990610g
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Surfaces Using Optically Manipulated Colloidal Particles

Abstract: Optical trapping techniques have been used extensively to manipulate biological objects and micrometer-sized colloids in a wide variety of investigations. We have used an extension of this technique, scanning laser optical trapping, to simultaneously trap multiple colloids in a designed pattern and have locked-in this artificially created structure through photopolymerization of the monomer-containing solvent. This technique can be used as a means of constructing templates for lithography or as a starting poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…When the beam illuminates a different position, the object is again released and free to diffuse out of the trap location. However, the particles must not escape out of the range of the trapping beam to be retrapped and therefore the scanning cycle must be sufficiently fast [92,93] Fig. 2).…”
mentioning
confidence: 99%
“…When the beam illuminates a different position, the object is again released and free to diffuse out of the trap location. However, the particles must not escape out of the range of the trapping beam to be retrapped and therefore the scanning cycle must be sufficiently fast [92,93] Fig. 2).…”
mentioning
confidence: 99%
“…Moreover, a colloidal crystal can be grown on a template, whose geometry influences the crystal structure [32][33][34][35]. It is reported that crystals nucleate (heterogeneous nucleation) initially in the fluid layer nearest to the smooth wall then propagate rapidly throughout the plane after layering is completed.…”
Section: Resultsmentioning
confidence: 99%
“…[32] The dielectric particles are drawn into the region of highest light intensity and accelerated in the direction of the light propagation by the radiation pressure. [33] If three laser beams are brought to interference at a substrate surface, a standing wave 2-D pattern is generated, which allows entrapping of particles in the virtual lattice geometry of the interference pattern. An extension of this technique, called scanning laser optical trapping, was used to simultaneously trap multiple colloids in a designed pattern which was locked-in by photopolymerization of a monomercontaining solvent (Fig.…”
Section: Optical Fieldsmentioning
confidence: 99%